2014
DOI: 10.1126/science.1253596
|View full text |Cite
|
Sign up to set email alerts
|

Cdc48 and a ubiquitin ligase drive disassembly of the CMG helicase at the end of DNA replication

Abstract: Chromosome replication is initiated by a universal mechanism in eukaryotic cells, involving the assembly and activation at replication origins of the CMG (Cdc45-MCM-GINS) DNA helicase, which is essential for the progression of replication forks. Disassembly of CMG is likely to be a key regulated step at the end of chromosome replication, but the mechanism was unknown until now. Here we show that the ubiquitin ligase known as SCF(Dia2) promotes ubiquitylation of CMG during the final stages of chromosome replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
302
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(336 citation statements)
references
References 56 publications
21
302
0
Order By: Relevance
“…The arrested fork, with the help of DNA polymerase, helicase, and topoisomerase (5), merges with the fork approaching Ter from the opposite direction, and the resulting catenated daughter molecules are resolved by topoisomerase IV in bacteria (6) and topoisomerase II in eukaryotes (7,8). In budding yeast, the unloading of the replisomal components from the template after replication termination is facilitated by Cdc48 and a ubiquitin ligase (9).…”
mentioning
confidence: 99%
“…The arrested fork, with the help of DNA polymerase, helicase, and topoisomerase (5), merges with the fork approaching Ter from the opposite direction, and the resulting catenated daughter molecules are resolved by topoisomerase IV in bacteria (6) and topoisomerase II in eukaryotes (7,8). In budding yeast, the unloading of the replisomal components from the template after replication termination is facilitated by Cdc48 and a ubiquitin ligase (9).…”
mentioning
confidence: 99%
“…During replication termination, CMG unloading was shown to involve polyubiquitylation of MCM7 by using K48-linked chains (33,34). To compare p97-mediated helicase unloading during ICL repair and replication termination, pICL or an undamaged control plasmid (pControl) was allowed to replicate in extract.…”
Section: Resultsmentioning
confidence: 99%
“…3D, 4, and 5B) (33,34). Although K48 linkages play a prominent role in protein turnover, proteasomal degradation was not required for helicase unloading (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has shown that Schizosaccharomyces pombe cells elicit a program to degrade replisome upon DNA replication stress through the action of the ubiquitin-proteasome system SCF Pof3 , a homolog of the budding yeast SCF Dia2 ubiquitin-proteasome system (Roseaulin et al 2013a,b). Because Ctf4 physically interacts with Dia2, which drives CMG helicase and replisome disassembly at the end of DNA replication (Maric et al 2014;Moreno et al 2014) and is ubiquitylated by SCF Dia2 (Ho et al 2002;Collins et al 2007;Mimura et al 2009;Morohashi et al 2009), one possibility could be that Ctf4 is targeted by Dia2 in response to replicative stress in a way dependent on H3K56ac. However, because the ctf4-DNT mutation that preserves the Ctf4 interaction with Dia2 (Mimura et al 2009;Morohashi et al 2009) does not restore the viability of asf1D rrm3D cells and is lethal in the rrm3D mutant (in contrast to the ctf4-NT mutation that loses the Ctf4-Dia2 interaction), we exclude the possibility that Ctf4 action could be regulated during replicative stress by H3K56ac through an action mediated by the SCF Dia2 .…”
Section: Discussionmentioning
confidence: 99%